THE ROLE OF PRIVATE CAPITAL INFLOWS AND THE EXCHANGE MARKET PRESSURE ON REAL EXCHANGE RATE APPRECIATION: THE CASE OF TURKEY - (:unkn) unknown (WILEY, 2013)
The aim of this paper is to investigate the role of different private capital inflows and the exchange market pressure (EMP) on the real effective exchange rate (REER) appreciation of the currency in Turkey. To that end, the paper first investigates the long-run equilibrium relationship and then employs Granger causality analysis. Results of the bounds test for cointegration within the autoregressive distributed lag (ARDL) modelling approach of Pesaran . (2001) reveal level relationship between the diverse private capital inflows, EMP and REER. Granger causality analysis suggests that there is a unidirectional causality running from all the concerned private capital inflows and EMP to REER. The ARDL model shows first that the impact of bank liabilities and portfolio investment liabilities are almost equal, high and positive. Second, foreign direct investment and workers' remittances have a negative but statistically insignificant effect. Third, EMP mitigates REER appreciation of the currency in Turkey. The empirical results suggest that speculative portfolio investment liabilities but particularly bank liabilities with short maturities should be better managed; more flexibility should be introduced to the floating exchange rate regime to avoid loss of competitiveness related with capital inflows; whereas foreign direct investments and remittances should be encouraged.
Keywords: F21; F24; F32; F31; International investment; long-term capital movements; remittances; current account adjustment; short-term capital movements; foreign exchange; TIME-SERIES; REMITTANCES